The Effect of Optimized Ultrafiltration on Perioperative Pulmonary Function During Cardiopulmonary Bypass in Infants Under 10 kg - Jianhong Niu; Guangdi Zhai; Aibin Zheng; Juanying Zhou; Shengqi Jiang; Jianping Ma (Frontiers Media S.A., 2021)
Objective: This study aims to investigate the effect of optimized ultrafiltration on perioperative electrolytes, acid-base balance, and pulmonary function during cardiopulmonary bypass (CPB) in infants with low body weight (under 10 kg), using traditional balanced ultrafiltration and modified ultrafiltration.Methods: A total of 30 children who underwent surgical correction for congenital heart disease in Changzhou Children's Hospital between January 2018 and December 2019 were randomly divided into two groups. In the treatment group, ultrafiltration pre-treatment was carried out with blood-containing priming fluid prior to CPB. Balanced ultrafiltration was performed during the operation, and optimized and modified ultrafiltration were conducted before closing and extubation. In the control group, traditional balanced ultrafiltration was used during the operation, and a modified ultrafiltration combination was used before closing and extubation. Indexes such as blood gas analysis and electrolytes were measured perioperatively, and pulmonary function was observed.Results: No deaths were reported in either group. The ventilator-assisted breathing time was shorter in the treatment group than in the control group (P < 0.05). The indexes of the treatment group were closer than those of the control group to the optimal physiological values. The concentrations of potassium ion (K+), lactate (Lac), and blood glucose (Glu) decreased, and there was significant difference between the two groups (P < 0.05) at the end of CPB. Hemoglobin (Hb) and hematocrit (HCT) in the treatment group increased (P < 0.01). Alveolar-arterial differences for oxygen (A-aDO2) and respiratory index (RI) increased significantly in both groups after operation. Children in the treatment group began to recover lung function earlier than children in the control group. Both A-aDO2 and RI were lower in the treatment group than in the control group at each time point after operation (P < 0.05).Conclusion: Optimizing and modifying the traditional ultrafiltration combination method can effectively shorten the ultrafiltration time, reduce the adverse impacts of the ultrafiltration technique, and improve the lung function of infants after operation.